2005
DOI: 10.1038/nature03886
|View full text |Cite
|
Sign up to set email alerts
|

Hassall's corpuscles instruct dendritic cells to induce CD4+CD25+ regulatory T cells in human thymus

Abstract: Hassall's corpuscles-first described in the human thymus over 150 years ago-are groups of epithelial cells within the thymic medulla. The physical nature of these structures differs between mammalian species. Although Hassall's corpuscles have been proposed to act in both the removal of apoptotic thymocytes and the maturation of developing thymocytes within the thymus, the function of Hassall's corpuscles has remained an enigma. Here we report that human Hassall's corpuscles express thymic stromal lymphopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
558
1
19

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 685 publications
(593 citation statements)
references
References 26 publications
15
558
1
19
Order By: Relevance
“…In agreement, it was recently suggested that human Treg-cell progenitors may selectively reside within mature DP thymocytes expressing high levels of CD69 and TCR-ab, since these cells develop into CD4SP Treg cells in response to activated autologous plasmacytoid and myeloid DCs [40], although not excluding the possibility of FOXP3 induction at the SP stages [41,42]. Additionally, our multiple regression analyses show a significant statistical dependency of the FOXP3 1 DP and SP populations, further supporting their direct precursor-product association.…”
Section: Discussionmentioning
confidence: 74%
“…In agreement, it was recently suggested that human Treg-cell progenitors may selectively reside within mature DP thymocytes expressing high levels of CD69 and TCR-ab, since these cells develop into CD4SP Treg cells in response to activated autologous plasmacytoid and myeloid DCs [40], although not excluding the possibility of FOXP3 induction at the SP stages [41,42]. Additionally, our multiple regression analyses show a significant statistical dependency of the FOXP3 1 DP and SP populations, further supporting their direct precursor-product association.…”
Section: Discussionmentioning
confidence: 74%
“…DC can differentiate T regs in the thymus [78] and in the periphery [79], and expand them once the T regs have formed [80][81][82]. Antigen-specific T regs are much more effective than polyclonal populations in suppressing immunity in vivo [79,[81][82][83].…”
Section: Tolerogenicity Another Side Of Immunogenicitymentioning
confidence: 99%
“…The expression of AIRE in the thymic MECs is believed to play a role in the negative selection of autoreactive T cells (4 -7), but another structure, the epithelial Hassall's corpuscle, seems to be important in the positive selection of human CD25 ϩ Treg cells (31). We therefore examined the relationship of AIRE ϩ cells and Hassall's corpuscles in four different thymic tissues.…”
Section: Expression Of Aire In Human Thymusmentioning
confidence: 99%